Histological Characterization of Biliary Intraepithelial Neoplasia with respect to Pancreatic Intraepithelial Neoplasia - Yasunori Sato; Kenichi Harada; Motoko Sasaki; Yasuni Nakanuma (International Journal of Hepatology)
Biliary intraepithelial neoplasia (BilIN) is a precursor lesion of hilar/perihilar and extrahepatic cholangiocarcinoma. BilIN represents the process of multistep cholangiocarcinogenesis and is the biliary counterpart of pancreatic intraepithelial neoplasia (PanIN). This study was performed to clarify the histological characteristics of BilIN in relation to PanIN. Using paraffin-embedded tissue sections of surgically resected specimens of cholangiocarcinoma associated with BilIN and pancreatic ductal adenocarcinoma associated with PanIN, immunohistochemical staining was performed using primary antibodies against MUC1, MUC2, MUC5AC, cyclin D1, p21, p53, and S100P. For mucin staining, Alcian blue pH 2.5 was used. Most of the molecules examined here showed similar expression patterns in BilIN and PanIN, in which their expression tended to increase along with the increase in atypia of the epithelial lesions. Significant differences were observed in the increase in mucin production and the expression of S100P in PanIN-1 and the expression of p53 in PanIN-3, when compared with those in BilIN of a corresponding grade. These results suggest that cholangiocarcinoma and pancreatic ductal adenocarcinoma share, at least in part, a common carcinogenic process and further confirm that BilIN can be regarded as the biliary counterpart of PanIN.